Implementasi model teams games tournament untuk meningkatkan motivasi belajar Bahasa Indonesia siswa kelas IV - Selly Pratito Ningrum; Nelly Rhosyida; Praja Mulyantoro (Indonesian Journal of Learning and Educational Studies, 2024)
improve learning outcomes. An interactive and collaborative learning model, such as Teams Games Tournament (TGT), is considered capable of enhancing students' motivation through enjoyable and competitive activities. This study aims to determine the increase in students' motivation to learn Indonesian through the TGT (Teams Games Tournament) model. The research employed Classroom Action Research (CAR) and involved fourth-grade students at SDN Kaliajir, Sleman Regency, Yogyakarta Special Region. The data analysis technique used was descriptive quantitative analysis. The study results indicated that, in the pre-cycle phase, only 33% of students demonstrated high motivation scores. In Cycle I, the motivation of fourth-grade students who met the success criteria increased to 67%. By Cycle II, student motivation reaching the success criteria rose to 83%. Therefore, by Cycle II, the class motivation level met the established success criteria, with ≥75% of students present achieving a scale score with a minimum classification of high.